Astronomical Observations During Willem Barents's Third Voyage to the North (1596-97) - Van der Werf, Siebren Y. (ARCTIC, 1998)
During Willem Barents's third voyage to the North and the wintering on Novaya Zemlya (1996-97), many astronomical observations were made. Solar declinations quoted in the diary of Gerrit de Veer indicate that the journal dates are correct within three days and that the Gregorian calendar was used throughout. The much-debated premature return of the sun on 24 January 1697, when it was geometrically below the horizon, fits many, but not all, of the characteristics of the arctic mirage that is now known as the Novaya Zemlya effect. This same effect might also explain the controversial report of a conjunction of occurrence of Jupiter and the moon on 25 January 1597, when Jupiter would normally not have been visible. It is shown, however, that the occurrence of the conjunction during that night could have been concluded from following the positions of the moon and Jupiter for several hours. An analysis of latitude determinations made at the expedition's wintering place, Het Behouden Huys, indicates that typical measurements had an accuracy of 15'-20'. In the Novaya Zemlya region, the variation of the earth's magnetic field was about 30 W 400 years ago, and about 23 E in 1871, and it is about 32 E today. During the return voyage in two open boats, Barents died on 20 June 1597. A reconstruction of that part of the route is presented. A Dutch-Russian expedition search for Barents's grave in August 1995; however, it appears most likely that he was buried at sea. Le troisième voyage de Willem Barents vers le Grand Nord et son hivernage en Nouvelle-Zemble (1596-97), ont donné lieu à de nombreuses observations astronomiques. Les déclinaisons solaires citées dans le journal de Gerrit de Veer indiquent que les dates du journal sont correctes à trois jours près et que le calendrier grégorien y a été utilisé de façon constante. Le retour prématuré du soleil le 24 janvier 1597, retour qui soulève tant de débats, cadre bien avec la plupart (mais pas toutes) des caractéristiques du mirage arctique que l'on connaît maintenant ...